Pemanfaatan Alokasi Dana Desa (Add) Dalam Pembangunan Desa Didesa Tanjung Sidupa Kecamatan Pinogaluman Kabupaten Bolaang Mongondow Utara - Takaliuang, Rio Armando; Tulusan, Femmy; Sondakh, Telly (JURNAL ADMINISTRASI PUBLIK, 2015)
Abastrack: In accordance with the village development goals mandated in Law No. 6 of2014, thus, the Utilization of Village Allocation Fund (ADD) is expected by the GovernmentBolaang North Mongondow can increase community participation in rural development in mutualcooperation. Rural development is directed to make optimum use of natural resources and humanresources development by improving the quality of life, skills and initiative with guidance andassistance from the government.To find out how the Village Fund Allocation Utilization in promoting rural development inthe village of Tanjung Sidupa District of North Mongondow Pinogaluman Bolaang.As for the benefits of this research are: (1) Purpose Theoretical results of this study areexpected to be useful in the development of science related to the science of government. Especiallyin the analysis of the Village Fund Allocation Utilization (ADD). (2) Practical Uses results of thisstudy are expected to contribute ideas on the implementation of the policy to the perpetrators ofthe policy and decision makers related to the development of regional development.In this regard the government to increase the capacity of the village, development andempowerment of rural communities need to gain greater attention, including through the patternof allocation of funds pengelolahan village or the Village Fund Allocation (ADD). ADD isdistributed to all villages in North Mongondow Bolaang fair and equitable manner and its use inaccordance with the needs of the village.Based on the results of these studies in deduced that the utilization of the Village FundAllocation (ADD) as a replacement for the use of development funds / District Village can increasecommunity participation in village development in Tanjung Sidupa.Based on the conclusions of the research results it is suggested several things: (1) Tointensify community participation in rural development. (2) Create a bulletin board in every villageto announce the implementation report the use of ADD to be known by the whole community.Key Word :Village Fund Allocation (ADD), Rural Development